2018
DOI: 10.1021/acs.jpcb.8b03543
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Segregation in Alcohol–Water Binary Mixtures Is Driven by Water Clustering

Abstract: Previous neutron scattering work, combined with computer simulated structure analysis, has established that binary mixtures of methanol and water partially segregate into water-rich and alcohol-rich components. It has furthermore been noted that, between methanol mole fractions of 0.27 and 0.54, both components, water and methanol, simultaneously form percolating clusters. This partial segregation is enhanced with decreasing temperature. The mole fraction of 0.27 also corresponds to the point of maximum excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…Because of such an amphiphilic nature, the microscopic structures of hydrated methanol in liquid water have attracted noticeable attention. Several experimental approaches have shown that the anomalous thermodynamics of alcohol-water systems arises mainly from the incomplete mixing at the molecular level, which exhibits partially segregated microstructures, both into water-rich and alcohol-rich components depending on the relative concentrations [4][5][6][7][8][9][10][11][12]. In order to supplement or corroborate the experimental results, many computer simulation studies have been performed at different levels of sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…Because of such an amphiphilic nature, the microscopic structures of hydrated methanol in liquid water have attracted noticeable attention. Several experimental approaches have shown that the anomalous thermodynamics of alcohol-water systems arises mainly from the incomplete mixing at the molecular level, which exhibits partially segregated microstructures, both into water-rich and alcohol-rich components depending on the relative concentrations [4][5][6][7][8][9][10][11][12]. In order to supplement or corroborate the experimental results, many computer simulation studies have been performed at different levels of sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, from this geometrical analysis, it can be envisaged the presence of two competing effects at play in the solvent mixture: (i) the requirement to satisfy all of the hydrogen bonds available sites, a job that is mainly left to water molecules, that are small and flexible as they form slightly longer HBs among themselves and with the solutes and (ii) the requirement to accommodate and increasing number of very weakly interacting polar groups (so weakly, that in the scale that we can detect with the combination of neutrons and EPSR simulations, it doesn't make any difference if charges are present or not 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 The problem of the causes of conon-solvency therefore intersects and has implications for the long-standing debate on the hydrophobic effect and the observed excess order in alcohol/water mixtures. 6 In these 17 years of publications and particularly in a very recent re-visitation of the topic, 7 the full power of combining neutron diffraction with isotopic substitution (NDIS) 8 and a simulation 2 method developed specifically for the interpretation of total scattering data from molecular liquids, the empirical potential structure refinement (EPSR) 9 has been exploited. The main findings can be summarised as:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the influence of structural characteristics and hydrogen bonds on kinetic characteristics will not be revealed. A similar analysis with the use of the all-atom potential for water-alcohol rats was carried out in [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%